Proceedings of 5th International Conference on Construction Applications of Virtual Reality - CONVR 2005 - - Dias, J.; Ana Rita Leitao (2005)
Welcome to the CONVR 2005 Programme! This year we are pleased to organise the 5th Conference on Construction Applications of Virtual Reality 2005 at CCIR (Centre for Construction Innovation and Research) based in the School of Science & Technology at the University of Teesside, Middlesbrough, U.K., where the first CONVR2000 was held. Subsequent conferences were held in 2001 in Chalmers (Sweden), in 2003 in Blacksburg (Virginia, USA) and, in 2004, in Lisbon (Portugal). Exciting and wide-ranging technical and industrial VR application papers were presented at these conferences with the participation of researchers and industry delegates from many countries. CCIR has taken the opportunity to host the fifth CONVR conference, a rich international forum for research and debate on the current initiatives and future challenges of Virtual Reality (VR) and Augmented Reality (AR) in Architecture, Engineering and Construction (AEC). Durham is one of the historical cities in the North East of England. Its historic city centre and the magnificent Cathedral and Castle which are included in the UNESCO World Heritage List lie on a rocky peninsula formed by a loop of the river Wear. Virtual Reality (VR) is an exciting new technology that offers considerable potential benefits for all stages of Architecture, Engineering and Construction processes, from initial planning and conceptual design to facility management and operations. Augmented Reality (AR) is a natural evolution of the VR technology; it allows the user to see the real world, with virtual objects superimposed upon or registered with the real world. Therefore AR supplements reality, rather than completely replacing it. VR and AR can be applied as a vehicle for the whole life cycle design and operation of AEC projects. Sustainable research efforts throughout the world are pushing the frontier of knowledge in terms of utilizing and implementing VR and AR. The mission of the conference is to bring together scientists, researchers, practitioners and industrialists in all areas of Architecture, Engineering and Construction and promote efficient exchange of ideas and develop mutual understanding of the needs and potential applications of VR and AR technologies. The objective of the conference is to report and disseminate outputs/progress/ideas of innovative international research activities in this field and formulate strategies for future research directions. In response to the issued call for papers the programme committee has received 21 communications from which 6 full papers and 11 short papers were selected, after being peer reviewed by at least 3 reviewers each. Submissions have been originated from all over the world. The CONVR2005 meeting promoted Scientific, Industrial and Social Programmes. The Scientific Programme included an Industrial day (12th September) with 8 invited key-note presentations (40 minutes), and two panels (“Technology Uptake by Industry” and “The role of academia to facilitate Technology Transfer to the Industry”). The invited key-notes were as follows: Prof. Ghassan Aouad and Angela Lee, University of Salford, “Advances in application of VR technologies: the nD initiative.” Mr. Tony Brown, Virtalis, “Empowering end-users of building facilities using the power of VR” Prof. Tom van Vuren, Mott MacDonald, UK, “Microsimulation in transport modelling - advances in 4D visualisation” Engº Serafim Castro, MotaEngil, Portugal, “Automatic road construction planning: the ROADSIM project” Prof. N Dawood, University of Teesside, “Application of 4D in the heavy civil engineering industry: the white-city experience.” Prof. Ammar Kak and Prof. Emanuele Trucco, HW University, “Computer vision and its application to manage site construction activities.” Prof. Miguel Dias, ADETTI/ISCTE, Portugal, “Augmented reality and its application to the construction industry” The following two programme days included paper presentations, 2 key-note presentations and short papers. The invited key-notes were as follows: Prof. Terrence Fernando, Univ. of Salford, UK, “Future Spaces” Chris Allen and Peter Moyes, A3D, UK, “Commercial use of 4D planning and 3D for asset management”) The programme included also a banquet and a belly dance show. The proceedings of the Conference will be published in electronic format, in a special edition of the VIRtual journal (http://virtual.inesc.pt/convr2005), as well as CD. This programme is the result of much hard work and sincere devotion of a large number of volunteers and support of several institutions. The presidency of the organising committee and programme committee would like to express a word of thanks, to all that have contributed to the organisation of this event: to the members of the organising committee and, in particular, Claire Leonard and Rita Pannen (Univ of Teesside) and Ana Rita Leitão (Adetti), for the enthusiastic and professional commitment to the numerous tasks of the production of such an event; to the members of the programme committee and external reviewers for the motivation and attention dedicated to the evaluation and selection of the works submitted; to the invited speakers, Prof. Ghassan Aouad, Ms Angela Lee, Mr. Tony Brown, Prof. Tom van Vuren, Mr. Mott MacDonald, Engº Serafim Castro, Prof. N Dawood, Prof. Ammar Kak, Prof. Emanuele Trucco, Prof. Miguel Dias, Prof. Terrence Fernando, Mr. Chris Allen and Mr. Peter Moyes, for making the time to share their knowledge and experience with the participants; to the authors of all submitted works, for their motivation, commitment and effort put into the writing of their works. We would finally like to thank all the people and institutions that supported the 5th Conference on Construction Applications of Virtual Reality: CCIR, UK University. of Teesside, UK Virginia Tech, USA VR-NET, UK ADETTI - Associação para o Desenvolvimento das Telecomunicações e Técnicas de Informática , Portugal ISCTE, Portugal GPCG - Grupo Português da Computação Gráfica, Eurographics Portuguese Chapter Construction Excellence in the NorthEast, UK Construction Productivity Network, UK Cyberchair Virtalis, UK Mota Engil, Portugal Durham, September 2005 Nash Dawood, Chair Walid Thabet, Scientific Co-Chair José Miguel Salles Dias, Scientific Co-Chair https://arquivo.pt/wayback/20060929022957/http://www.adetti.pt/events/CONVR2005/